Matching feed energy resources to energy requirements of working cattle in semi-arid areas - Israel, Stanley Hemed (The University of Edinburgh, 2000)
The objectives of this thesis were to study the effects of workload and level of feeding on work and live weight changes of draught oxen; to study the effects of energy supply on work performance of oxen; to explore and/or assess strategies to improve the effectiveness of supplementary feeding for draught cattle; and to test the recommended standards for feeding draught cattle under semi-arid conditions in South Africa.

Four experiments were carried out in South Africa. In experiment 1, the effects of three workloads on work and live weight change of three teams each of four draught oxen fed at the same level (1.3 x their ME requirement) were studied. The workloads were: (1) heavy (estimated energy expenditure of 0.9 x maintenance); (2) medium (0.6 x maintenance); (3) low (0.3 x maintenance). Work consisted of pulling sledges loaded differently over different distances for each team.

Experiment 2 studied the effect of level of energy supply during work on the performance of draught oxen. Six pairs of oxen were assigned to two treatments. In treatment 1 oxen were fed on a low energy (0.8 x maintenance) diet during part 1 (week 1-7) followed by a high energy (1.8 x maintenance) diet in part 2 (week 8-13) of the study. In treatment 2 they were fed on the high energy diet throughout. Oxen on both treatments did the same work pulling loaded sledges so that their estimated energy expenditure for work was 0.9 x maintenance.

Experiment 3 assessed two strategies of supplementing draught cattle. In treatment 1 oxen were supplemented for 7 weeks before working and for 7 weeks while working. The supplements were cobmeal (1.5 kg/head/day) and lucerne (0.5kg/100kgLW/day). In treatment 2 the same supplements were fed for the 7 working weeks at twice the amount in treatment 1. Six pairs of oxen were assigned to the two treatments. All oxen were fed on restricted amounts (0.8 x their ME requirements) of Chloris gayana hay. Work done was the same as that of experiment 2.

Experiment 4 assessed practices adopted by farmers when using supplements to improve the effectiveness of maize stover as feed for working oxen. Three supplements were fed to 6 pairs of oxen in three periods (a 3x3 latin square design). The supplements were lucerne (2.5 kg/head/day), sunflower cake and cob meal (both at 3.6 kg/head/day). Maize stover was fed ad libitum. During each period oxen were fed the diet for two weeks before they worked for two weeks. Work done was similar to that of experiment 3.

The recommended feeding standards for draught cattle were tested by studying the energy balances and live weight changes of oxen in the four experiments.

In experiment 1, live weight changes of oxen under the three treatments suggested that animals subject to the heavy workload utilised dietary energy more efficiently and they were less selective in their eating. The speeds of working of oxen on the three treatments decreased with increase in workload but the differences were not statistically significant (p>0.05). Oxen tended to increase their walking speed towards the end of working in the morning when heading home. Within treatment 1, heavy oxen (>400kg LW) lost body weight while light oxen (<400kg LW) registered weight gains during the same period.

In experiments 2 and 3, oxen fed a low energy diet or not supplemented before work lost body weight and condition progressively. The same oxen regained some of their body weight and condition when offered the high energy diet or supplement while working. Oxen that received high energy diet or supplement both before and during work maintained their body weights. In both experiments, there were no significant differences (p>0.05) in work done by oxen on low energy or not supplemented before work and those on high energy or supplemented both before and during work, respectively. The experiments showed that loss of body weight and condition in work oxen could occur without affecting their work performance. The results suggest that energy needed for work could be obtained from body energy reserves or equally efficiently directly from offered food. This implies that it may not be necessary to supplement draught oxen during the dry season before work begins provided the oxen do not lose weight to the extent of compromising their capacity for work. Both strategies of feeding supplements to draught oxen in experiment 3 had some effects on weight changes that could be beneficial, but if there is no risk of compromising the working capacity as a result of weight loss, supplementation could be confined to the period of working so as to reduce labour costs.

In experiment 4, methods used by farmers to feed supplements did not take nutritive value into account. Supplementation with sunflower cake, lucerne and cob meal to oxen fed on maize stover had no influence on their work performance. There were statistically significant (p<0.05) differences between the three supplements in amount of stover consumed and live weight gain. Oxen supplemented with sunflower cake consumed more stover and attained larger weight gains than the others.

Study of the energy balances of oxen in the four experiments showed that oxen working in a team contribute differently to the overall work done and this leads to inaccurate estimates of energy balance for individual animals working in teams. Estimates of energy balance for whole teams were more reliable. Oxen working in pairs gave better estimates than those of oxen working in teams of four.

Feeding standards for cattle used for work were found to be broadly correct in semiarid areas.